Pengaruh Variasi Diameter dan Jarak Nosel Terhadap Daya dan Efisiensi Turbin Pelton - Sarjono Sarjono (Jurnal Teknologi, Fakultas Teknologi Industri, Institut Sains & Teknologi AKPRIND Yogyakarta, 2021)
The purpose of this study was to determine the effect of variations in diameter and number of nozzles on the power and efficiency of the Pelton turbine. The research method is experimentally using a miniature Pelton turbine installation with 3 nozzles. Variations in nozzle diameters of 4 mm, 5 mm, and 6 mm with a nozzle distance of 80 mm, 90 mm, and 100 mm and variations in rotation from 300 to 700 rpm. The results showed that the nozzle diameter of 6 mm and the distance of the nozzle to the blade of 80 mm produced maximum turbine power and efficiency, namely 30.00 watts and 34.79%, respectively.